Creating a Low-Cost Dryer for Javanese Cardamom (Amomum compactum) to Empower Farmers Group in Burno Village, Senduro District, Lumajang Regency - Wirayudhana, I Ketut Satya; Roykhana Purwita; Tonggi Simanjuntak; Dyah Rahmawati Hizbaron (Direktorat Pengabdian kepada Masyarakat, 2024)
The conventional approach to dry cardamom using sunlight is ineffective to be conducted in village that has high rain intensity and low ambient temperature. In the dry season, cardamom needs to be dried for 4-5 effective days, meanwhile, when it's the rainy season, it would take 14-16 days. The weather and the high prices of dryer machines in Burno Village, Senduro District, Lumajang Province, Indonesia, force the cardamom farmers to sell their cardamom in the form of wet cardamom, although it would reduce 80% of their revenues. This program aims to create a low-cost cardamom dryer to empower farmer groups in Burno Village to make their own dryer from used goods. Collaborating with the Tanirejo farmer group, this program managed to create a prototype of a dryer machine for cardamom which will reduce the drying time by 86% from 2,090 minutes to 277 minutes. By implementing this low-cost dryer, farmers can dry their cardamom efficiently, increase their revenue, and improve their overall economic stability.